Improving Graduate Competence in Physical Training and Sports Student Training Programs at Surabaya State University - Jatmiko, Tutur; Sidik, Rizky Muhammad; Utami, Tri Setyo; Aji, Wahyu Renandi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Community empowerment is an essential effort focused on fostering change in different areas, including athletics, social sciences, arts, and local culture. In the realm of sports, community empowerment aims to improve the quality of human resources, athleticism, and performance at provincial, national, and even global levels. It acts as a tool for molding community identity and is vital for the advancement of sports. A goal of this Community Empowerment Program (PKM) is to provide certified training for physical trainers to students in the Vocational Faculty and the Sports Science and Health Sports Study Programs within the Health Faculty. This initiative seeks to promote sports accomplishments at both student and wider levels, encompassing regional, provincial, national, and international tiers. Developing sports success through a systematic, enduring, and sustainable approach is crucial for creating sports excellence as a regional trait and national identity. Community engagement plays a vital role in influencing national sports policies and programs. The enhancement of sports via the Sports Study Program at FV and FIKK is crucial for achieving both community involvement in sports and sports success. The techniques used consist of training physical trainers and the creation of programs. Physical trainer training emphasizes creating physical conditioning that meets the requirements of particular energy systems, sport traits, and periodization to improve athletes' biomotor abilities. Moreover, attendees are taught how to create physical training plans to enhance athlete performance and achieve established goals. This program aims to prepare FV and FIKK sports students to create training plans that improve athlete performance and lead to success. The aim is to develop proficient coaches and top-performing athletes capable of representing East Java and Indonesia in various competitive arenas.